Blending the appearance of all-ceramic crowns in fluorosis condition with direct chair-side technique / Siti Mariam Ab Ghani ... [et al.] - Ab Ghani, Siti Mariam (Faculty of Dentistry, 2015)
Dental fluorosis incidence had been reported to be affecting children widely, especially in water-fluoridated area. As these children grow into young adults, perceived aesthetic problems arise mainly due to their concern with generalized mottled and stained teeth appearance. Fixed prosthodontics treatment involving single anterior tooth in patients with generalized fluorosis condition had been found challenging due to aesthetic restorability to blend with fluorosis condition. Clinical considerations: A simplified procedural direct chair-side technique of mimicking fluorosis condition onto anterior all-ceramic crowns are discussed in this paper. The mimicked fluorosis is reversible and has the opportunity to be adjusted according to the patient's fluorosis condition thus hindering the need to redo the crown in the future. Conclusions: The appearance of anterior all-ceramic crowns with direct chair-side staining technique provided blended and harmonized well with the dental fluorosis condition in both patients thus, giving natural looking smile.